Bioenergy potential and technical feasibility assessment of residues from oil palm processing: A case study of Jalapa, Tabasco, Mexico. (November 2020) - Ordoñez-Frías, E.J.; Azamar-Barrios, J.A.; Mata-Zayas, E.; Silván-Hernández, O.; Pampillón-González, L.
Abstract: Bioenergy around the world has proved to be a feasible strategy in terms of environmental, social and economic advantages for the development of our society. Nevertheless, in low- and middle-income countries, wood is the most traditional common biomass resource. At the same time, there is a wide variety of residues from industry processing that can be valorized. In recent years, oil palm production in Mexico has increased significantly; giving rise to the establishment of extraction plants whose process focuses mostly on oil extraction, disregarding solid by-products. The lack of proper management of these residues impacts the environment by piling up without control, open burning or left on the ground. For these reasons, this study aimed to assess the bioenergy potential and identify the most feasible technologies for the sustainable use of oil palm residues. Oil palm residues (fruit fiber, palm kernel shells and empty fruit bunches) were characterized by proximate analysis, calorific value and energy dispersive spectroscopy. A weighted decision matrix was designed to weigh the biomass conversion technologies considering sustainability criteria (environmental, technical, economic and social). As a result, a biomass and energy potential of 33, 416 t y −1 and 564.05 TJ y −1 were calculated for Tabasco palm oil sector. Pelletization of residue for thermal applications, followed by anaerobic digestion turned out to be the most feasible technologies for oil palm residue according to the regional context. An opportunity for pellet production from these residues was observed; this could be an alternative to substitute fuel wood and promotes modern bioenergy applications. Graphical abstract: Image 1 Highlights: Oil palm residues can offer bioenergy opportunities in southern Mexico. The weighted decision matrix can be an accessible tool for technical feasibility analysis. Pelletization and anaerobic digestion result the most feasible technology for OPR. Rural communities could meet their energy needs from utilizing oil palm residues. Opportunities for management plants and certification programs were revealed.